2009
DOI: 10.1016/j.cor.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling of coupled tasks and one-machine no-wait robotic cells

Abstract: Coupled task scheduling problems were first studied more than 25 years ago. Several complexity results have been established in the meantime, but the status of the identical task case still remains unsettled. We describe a new class of equivalent one-machine no-wait robotic cell problems. It turns out that scheduling of identical coupled tasks corresponds to the production of a single part type in a robotic cell. We describe new algorithmic procedures to solve this robotic cell problem, allowing lower and uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…This motivates Brauner et al (2009) to link the problem to a class of cyclic production scheduling problems, namely the one-machine no-wait robotic cell problem. They showed that minimizing the makespan for the single-machine identical coupled task scheduling problem is equivalent to maximizing the throughput rate in a one-machine no-wait robotic cell with the characteristics of having an input station (IN ), an output station (OU T ), and one machine (M ).…”
Section: Cyclic Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…This motivates Brauner et al (2009) to link the problem to a class of cyclic production scheduling problems, namely the one-machine no-wait robotic cell problem. They showed that minimizing the makespan for the single-machine identical coupled task scheduling problem is equivalent to maximizing the throughput rate in a one-machine no-wait robotic cell with the characteristics of having an input station (IN ), an output station (OU T ), and one machine (M ).…”
Section: Cyclic Schedulingmentioning
confidence: 99%
“…The instances set includes a total number of 250 instances with 20 to 500 jobs, where the task processing times are in the range of 10 and 100, and the delay durations in the range of 300 and 1,300. Ahr et al (2004); Li and Zhao (2007); Brauner et al (2009);Blazewicz et al (2012) adopted a similar approach, i.e., taking values from a discrete uniform interval. The instances in Sherali and Smith (2005) consist of 8 to 14 jobs, with aj taken from the normal distribution with a mean of 30 time units and a standard deviation of 5 time units, i.e., N (30, 5).…”
Section: Previous Instance Generation Schemesmentioning
confidence: 99%
“…The SFR used in this automated cell was a part of the computer-integrated manufacturing system CIM-2000 Mechatronics manufactured by DEGEM Systems Company. A real-life radar scheduling problem, which is equivalent to single machine SFRC with no-wait pick up scenario, was studied in [17]. They proved a radar system can be simulated by a no-wait SFRC due to the fact that the first task is a wave transmission and the second task is reflected wave receiving without delay.…”
Section: Related Researchmentioning
confidence: 99%
“…Regardless of swap ability, the majority of the results related to no-wait pickup category can be found in the research by Hall and Sriskandarajah (1996), Kats and Levner (1997), Levner et al (1997), Agnetis (2000), Agnetis and Pacciarelli (2000), Liu and Jiang (2005), Brauner et al (2009), Che and Chu (2009) and Che et al (2011). Therefore, the authors begin with fundamental definitions and concepts of a cyclic production in section 2.…”
Section: Introductionmentioning
confidence: 99%